Modelo de formação na área de reabilitação do projecto H-KNOW - Alfredo Soeiro (2009)
H-KNOW project means "Advanced Infrastructure for Knowledge Based Services for Restoring Buildings". It is part of FP7, sub-program Project Collaboration Aimed at Small and Medium Enterprises (SMEs). It has a total funding of the European Commission about 1.9 M € and a cost of about 2.6 M €. Has fifteen partners from five countries. The project is the existence of a growing number of complex works of rehabilitation of buildings that require quick and systematic knowledge of this specific type of work. A promising approach to facilitate such access is by providing SMEs of the construction and rehabilitation knowledge through collaborative business networks formed by these companies and partners to research and development (ID). One consequence of this project is to create a model for training and training using digital media. What emerges is a model with multiple facets and is meant to cover the diversity of needs and literacy in the field of rehabilitation.